MEMBANGUN LINGKUNGAN SEKOLAH AMAN (EDUKASI ANTI BULLYING BERBASIS KOMUNIKASI ASERTIF DI SMKN 1 KOTA TASIKMALAYA) - Ernawati; Hiaruman, Kayla Alliyah Diva; Wirasujatma, Muis; Fadila Wahab, Yanti; Rosyalia Widia Sofyan, Verra; Desty Puspatriani, Annisa (IKIP Siliwangi, 2026)
Bullying in schools remains a troubling global issue. Data from various national and international institutions shows that many students experience or witness bullying. Given the high number of bullying cases in schools, how can implementing anti-bullying education based on assertive communication reduce bullying and increase a sense of security in the school environment? Bullying can be prosecuted under several existing laws, both criminal and civil, as well as more specific regulations in the educational environment. Bullying violates Articles 310 and 311 of the Criminal Code concerning defamation and slander, which are often relevant to cases of verbal bullying or the spreading of rumors. This research uses a qualitative approach with a case study method to gain an in-depth understanding of the effectiveness of the education program. Assertive communication is believed to be key to empowering students to defend themselves without violence, reject bullying behavior, and report incidents effectively.